Letter - Winstanley, E.
029-0121-001 Mr Carthy Telegraphic Address: "WHOLESALE MANCHESTER" Telephone: BLACKFRIARS 1212. Extension No. Please Address Your Reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C 6th and 7th editions; Western UNION 5 Letter; BENTLEY COMPLETE PHRASE; Bentley second phrase; A.1. Marconi, and private. 30th June, 1937 Our reference 9165/ST/JEM Your reference The Trades Union Congress General Council, Transport House, Smith Square, LONDON. S.W.1. Dear Sirs, We now have pleasure in attaching hereto invoices in respect of goods sent forward for shipment by the s.s. Marian Moller from London to Gijon, which you will doubtless find in order. Up to the present, we have not received advice of the final sailing date of the steamer and consequently have not received insurance cover note or the charges. We will, therefore, pass you charges for insurance at a later date (at the rate of 75/-%) and meanwhile beg to remain, Yours faithfully, E. Winstanley Export Department, P.S. Since writing the above we have been advised by the Steamship Company that the final sailing date of the s.s. Marian Moller is Monday 5th July. 292/946/29/121